Medical practitioners' experiences and considerations when managing sleep medication for adolescents and young adults<subtitle>A qualitative study on general practitioners' and child and adolescent psychiatrists' reflections on their prescription and deprescription practices of sleep medication for 13-24-year-olds</subtitle> - Nanna Maria Andersen; Ásthildur Árnadóttir; Tora Grauers Willadsen; Gritt Overbeck (Taylor & Francis Group, 2024)
Introduction The prevalence of sleep disorders and use of sleep medication, particularly melatonin, are rising among adolescents and young adults (13-24 years). In Denmark, melatonin is approved for use in children with autism and ADHD up to 18 years of age, with other prescriptions being off-label in these age groups. The perspectives of medical practitioners on prescribing sleep medications to this age group remain largely unexplored.Aim This study aims to investigate the considerations of general practitioners (GPs) and child and adolescent psychiatrists (psychiatrists) when prescribing and deprescribing sleep medications for 13-24-year-olds.Methods We conducted qualitative semi-structured interviews with 10 GPs and six psychiatrists. Data were analyzed using an inductive approach.Results Psychiatrists typically prescribed melatonin with the expectation that deprescription would occur in general practice. Despite the universal goal of deprescription, it was hindered by various challenges. GPs identified patient motivation and a clear focus on deprescription as facilitative factors and expressed a need for enhanced emphasis on these aspects in general practice.Discussion and implications The findings align with existing prescription trends and literature on factors that promote and inhibit deprescription. The study underscores the complexities of deprescribing sleep medications for adolescents and young adults, suggesting the need for expanded guidelines and enhanced continuing education for GPs.Conclusions The research highlights significant discrepancies among medical practitioners regarding the deprescription process of sleep medications for young individuals, complicated by multiple factors. This underscores the need for better guidelines and further studies.